Mediators of the association between childhood body mass index and educational attainment: Analysis of a UK prospective cohort study. - Bowman, Kirsty; Cadman, Tim; Goncalves Soares, Ana; Robinson, Oliver; Hughes, Amanda; Heron, Jon; Segal, Alexa Blair; Huerta, Maria Carmen; Howe, Laura D. (Pediatric Obesity, 2023)
Summary: Background: Higher body mass index (BMI) in childhood is associated with lower academic achievement. Objective: To explore potential pathways linking childhood BMI with educational attainment. Methods: Using data from the Avon Longitudinal Study of Parents and Children prospective cohort study (N = 6949), we assessed the association between BMI z‐scores at 11.7 years and educational attainment at 16 (General Certificate of Secondary Education [GCSE] results). Depressive symptoms, externalizing behaviours, bullying and school enjoyment were considered as potential mediators. Mediators were examined individually and jointly using sequential causal mediation. Results: Higher BMI z‐scores were associated with lower GCSE scores (females β = −3.47 95% CI −5.54, −1.41 males β = −4.33 95% CI −6.73, −1.94). Together, bullying, externalizing symptoms, depressive symptoms and school enjoyment mediated 41.9% of this association in females, and 23.3% in males. In males, evidence for mediation was weak (confidence intervals for all indirect effects spanned the null). In both females and males, most of the mediation was driven by externalizing symptoms. Conclusions: The detrimental effect of higher BMI on educational attainment appears to be partly explained by externalizing behaviours, particularly in females. Interventions to support behavioural problems may help the academic achievement of children with a higher body weight.